Clinicomorphological Study for Preoperative Orthodontic Treatment of Mandibular Prognathism: Especially in Relation to Soft Tissue Profile - YASUDA, KAZUYUKI (The Japanese Journal of Jaw Deformities, 1991)
The author devised a method of measuring soft tissue in order to determine the patient's soft tissue profile (STP) in cases of mandibular prognathism.The purpose was to find a procedure for applying preoperative orthodontic treatment and a means of determining the mode of operation. Charts of STP standard deviation among normally occluded male and female patients were made. The relations among Groups A, B, C, D and E were investigated by measuring soft tissue according to Sanborn's classification modified by Tsuji, et al. From these studies we concluded that both the hard and soft tissues of each group were closely related. This information guided us as to the manner in which the surgical procedure would be approached. Each of the above 5 groups were eventually classified into 3 types prior to preoperative orthodontic treatment. Type1 Group A and E are characterized by forward protrusion of the chin and the upper and lower lips. They require labial tipping of the incisors of the mandibule, and occasionally lingual movement of the maxillary incisors in preoperative orthodontic treatment. Type 2 Group D is typically characterized by severe mandibular prognathism, and requires labial tipping movement of the upper and lower incisors in preoperative orthodontic treatment. In cases where the operation is done only on the mandibule, consideration of tooth axis inprovement is required so that the width of posterior displacement dose not exceed 15.0mm. Type 3 Group B and C are characterized by slight forward mandibular protrusion. The profile has pseudomandibular prognathism because of retrogression of the upper lip, and lower facial height. In preoperative orthodontic treatment, the overbite is shortened in order to decrease lower facial height. Postoperatively, the chin should be posteriorly receded and rotated upward. Furthermore, displacement shonld be minimized.